Penerapan Berbagai Permainan Estafet untuk Meningkatkan Kebugaran Jasmani Siswa Kelas X-2 SMAN 1 Gedangan Sidoarjo - Muhamad Cholid Izza Rasydi; Sasminta Christina Yuli Hartati; Supriyanto Supriyanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research is based on the behavior of the students in class X-2 at SMAN 1 Gedangan Sidoarjo, who have a sedentary lifestyle habit, which affects their physical activity and fitness. The aim of this research is to determine how much the relay game can improve the physical fitness of students in class X-2 at SMAN 1 Gedangan Sidoarjo. The research method used is Classroom Action Research (CAR) conducted over two cycles with a sample of 36 students from class X-2. Data collection was carried out using pre-tests and post-tests, and the data were analyzed and processed using descriptive percentage methods with IBM SPSS Statistics 26. The results show that there was an improvement in physical fitness components from cycle I to cycle II, with speed increasing by 8%, reaction speed by 11%, and agility by 2.5%. Based on the research conducted, it can be concluded that there was a significant improvement in physical fitness through the application of relay games for the students in class X-2 at SMAN 1 Gedangan Sidoarjo.